Persepsi Generasi Muda terhadap Program Makan Bergizi Gratis dan Dampak Kepercayaan Publik kepada Pemerintah - Aisyah Larasati Tambunan; Desliana Dwi Tamalia; Divi Humairah; Enggar Fibianingtyas; Ratna Indriani; Silvia May Jesica; Zahralia Albraina; Khoiriya Ulfah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines young people’s perceptions of the Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) and its impact on public trust in the government. The MBG program is one of the Indonesian government’s strategic policies aimed at improving nutritional quality, particularly for students, while supporting social welfare and human resource development toward Indonesia Emas 2045. In the digital era, social media plays a significant role in shaping public opinion, especially among Generation Z, who actively consume and disseminate information through online platforms. This research employed a qualitative descriptive approach with in-depth interviews, social media observations, and documentation studies as data collection techniques. The participants consisted of young people aged 18–25 years in Bandar Lampung selected through purposive sampling. The findings indicate that most informants perceive the MBG program positively because it is considered relevant to community needs, particularly in improving children’s nutrition and supporting economically vulnerable groups. However, public trust in the government remains conditional due to concerns regarding transparency, uneven distribution, food quality, and program supervision. The study also reveals that young people distinguish between support for the program itself and trust in the government as an institution. Positive perceptions of the program can increase political trust, but implementation weaknesses may reduce confidence in government performance. Therefore, transparency, consistency, and effective public communication are essential factors in strengthening public trust and ensuring the sustainability of the MBG program.